Current developments in the approach, diagnosis and treatment of preeclampsia - Jiménez, Alejandra Giselle Estrada; Trujillo, Zally Patricia Mandujano; Pirrón, Tomasa de los Ángeles Jiménez; Martínez, Rosa Martha Velasco; Ochoa, Sonia Rosa Roblero; Medina, María Fernanda Martínez (Seven Editora, 2024)
Introduction: Preeclampsia is a clinical syndrome, characterized by predominantly cardiovascular symptoms, manifestations attributable to systemic inflammation, endothelial dysfunction and generalized vasoconstriction resulting in hypertension, hypoperfusion and multiorgan failure. It affects between 3 and 10% of pregnancies, and is the leading cause of maternal death in the world. General objective: To know new strategies for approaching, diagnosing, and treating preeclampsia. Materials and methods: Articles in English and Spanish published from 2019 to 2022 were selected, using available electronic databases. Conclusions: New molecules have been discovered for the early diagnosis of preeclampsia, based on the angiogenic relationship, including high levels of sFlt-1, sEng, IL-16, Activin A, ICAM and VCAM, as well as low levels of PAPP-A, PlGF and placental protein 13. In addition, new drugs and treatments such as sildenafil, pravastatin, and stem cells are being researched for more effective management. However, due to discrepancies in outcomes for mother and fetus, its widespread recommendation is not yet possible. DOI:https://doi.org/10.56238/sevened2024.026-008